Entomological surveillance of invasive Aedes mosquitoes in Mazandaran Province, northern Iran from 2014 to 2020 - Seyed Hassan Nikookar; Ali Charkame; Asghar Nezammahalleh; Eslam Moradi-Asl; Ahmadali Enayati; Mahmoud Fazeli-Dinan; Mohammad Mehdi Sedaghat; Morteza Zaim (Scientific Reports, 2023)
Abstract Mosquitoes are the most important vectors of serious infectious diseases in the world. Dengue, Zika, chikungunya and yellow fever are emerging and re-emerging infectious diseases, associated with the distribution of two key vectors i.e. Aedes aegypti and Aedes albopictus throughout the world including countries neighbouring Iran. Entomological surveillance was planned and performed monthly from May to December during 2014–2020 in selected counties of Mazandaran Province, North of Iran, by ovitrap, larval collection, hand catch and human baited trap. Overall, 4410 Aedes specimens including 2376 larvae (53.9%) and 2034 (46.1%) adults belonging to six species, namely Aedes vexans, Aedes geniculatus, Aedes caspius, Aedes echinus, Aedes pulcritarsis and Aedes flavescence were collected and morphologically identified. Over the seven years of surveillance, Ae. aegypti and Ae. albopictus were not found by any sampling method. Aedes vexans and Ae. geniculatus were the most abundant species, their populations peaked in October and November and was positively correlated with precipitation and relative humidity. Aedes flavescence was a new species record for the province. A flowchart for planning and implementation of invasive mosquito surveillance for provincial health authorities in the country is proposed. These surveillance efforts provide basic and timely information for the health system to act promptly on integrated and intensified surveillance and control programs should Ae. aegypti and Ae. albopictus detected in the province.